2020
DOI: 10.1088/1755-1315/476/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude oil spillage on engineering properties of tropical residual soil

Abstract: Oil exploration in Nigeria causes serious environmental degradation. Little is known about the effects of crude oil spillage on soils found in northern Nigeria where oil exploration started less than two years ago (2018). This research is a comparative analysis of the effect of crude oil on contaminated and uncontaminated soil typically found in northern Nigeria. Five Trial pits were dug at Bayero University Kano, two of the trial pits were filled with 20 litres of crude oil while the remaining three trial pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…This was in agreement with the research carried out by Abosede (2013), Sari et al, (2018, Oyem and Oyem (2013). The research of Abdulfattah et al (2016), Precti and Shah (2015) reported from the research on hydrocarbon contaminated soil that electrical conduct can be affected by oil pollution. 3 revealed that apart from Ca, all others such as Na, K, Mg have all their CEC values below 10 cmolc/kg, this implies that the hydrocarbon pollutant greatly influenced the soil and therefore had negative impact on the soil ability to retain necessary and essential nutrients needed for plant growth.…”
Section: Resultssupporting
confidence: 89%
“…This was in agreement with the research carried out by Abosede (2013), Sari et al, (2018, Oyem and Oyem (2013). The research of Abdulfattah et al (2016), Precti and Shah (2015) reported from the research on hydrocarbon contaminated soil that electrical conduct can be affected by oil pollution. 3 revealed that apart from Ca, all others such as Na, K, Mg have all their CEC values below 10 cmolc/kg, this implies that the hydrocarbon pollutant greatly influenced the soil and therefore had negative impact on the soil ability to retain necessary and essential nutrients needed for plant growth.…”
Section: Resultssupporting
confidence: 89%
“…This generally concludes that for a road structure subjected to inundation by water, COCS should not be used where high CBR value is a requirement of the road structure and COCS remediated by the use of either charcoal or active carbon as filter media can be recommended for possible usage [1]. The CBR value generally decreases with increase in crude oil content, this trend is similar to those reported by [7] and [14]. From Figure 4 above, the CBR values are obtained at West African Standard compaction energy compaction, the 6.7% value obtained from the COCS does not meet the 80% minimum requirements for Type 1 base or sub-base materials for Nigerian roads nor does it meet the 20% minimum requirements for Type 2 sub-base materials for light trafficked roads but may be classified as sub-standard material for subbase by [1].…”
Section: California Bearing Ratio (Cbr)supporting
confidence: 62%
“…Negative effects of using crude oil contaminated soil for roads and building construction is further stressed when [14] observed a decrease in the MDD, CBR and cohesion of clay soil. These effects are further strengthened by the decrease in shear strength and an increase in compressibility of oil contaminated clay soil obtained by [15].…”
Section: Introductionmentioning
confidence: 99%